2021
DOI: 10.1021/acs.jpclett.1c02164
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy and Anharmonic Vibrational Analysis of (H2O–Krn)+ (n = 1–3): Hemibond Formation of the Water Radical Cation

Abstract: The hemibond is a nonclassical covalent bond formed between a radical (cation) and a closed shell molecule. The hemibond formation ability of water has attracted great interest, concerning its role in ionization of water. While many computational studies on the water hemibond have been performed, clear experimental evidence has been hardly reported because the hydrogen bond formation overwhelms the hemibond formation. In the present study, infrared photodissociation spectroscopy is applied to (H2O–Kr n )+ (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…This is in contrast to H 2 O + Rg n with the larger Rg atoms Ar and Kr, which have been grown and studied up to n = 14 and 3, respectively. 93,94 Fig. 6 summarizes the predicted evolution of the OH stretch and H 2 O bend frequencies n 1-3 as a function of cluster size for the size range n = 0-5 as basis for future IRPD spectroscopy and includes the available experimental data for n = 0 and 1 (Table S2 in ESI †).…”
Section: Pccp Papermentioning
confidence: 99%
“…This is in contrast to H 2 O + Rg n with the larger Rg atoms Ar and Kr, which have been grown and studied up to n = 14 and 3, respectively. 93,94 Fig. 6 summarizes the predicted evolution of the OH stretch and H 2 O bend frequencies n 1-3 as a function of cluster size for the size range n = 0-5 as basis for future IRPD spectroscopy and includes the available experimental data for n = 0 and 1 (Table S2 in ESI †).…”
Section: Pccp Papermentioning
confidence: 99%
“…Structures of the [H 2 O–X] + (X = He, Ne, Ar, Kr, CO 2 , N 2 O, and H 2 O) radical cation clusters have been studied by infrared (IR) spectroscopy in the gas phase. 21–31 Two structural motifs are confirmed: hydrogen bond (H-bond) and hemibond. The H-bonded type has a structure in which X is H-bonded to one of the OH groups of H 2 O + (HOH⋯X).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, however, it was found that the hemibond formation is favored over the H-bond formation in the cases of X = N 2 O and Kr. 30,31 Here, a question arises; what factors govern the competition between H-bond and hemibond formation.…”
Section: Introductionmentioning
confidence: 99%
“…The main experimental approach to hemibond formation has been observations of broad (σ, σ*) transitions of samples in the condensed phase. , On the other hand, spectroscopic and mass spectrometric studies of hemibonds in gas phase clusters have increasingly been reported. ,, Gas phase cluster studies enable us to explore microscopic details of hemibonds in model systems. One of the central issues in such cluster studies is the competition between hemibond and hydrogen bond (or proton transfer) with microsolvation by protic solvent molecules, such as water, methanol, and ammonia. , It has been demonstrated that an S∴S hemibond can be broken by microsolvation with a few molecules.…”
Section: Introductionmentioning
confidence: 99%